ANALYSIS OF LEGAL SOCIOLOGY THEORY FROM THE PERSPECTIVE OF MEDICAL LAW - Alawiyah, Tuti (Universitas prof. Dr. Moestopo (Beragama), 2025)
This study employs a socio-legal approach to examine how norms in medical law are not only formulated at the normative level but are also practiced, negotiated, accepted, or resisted within the daily interactions between doctors, patients, and healthcare institutions. Using a descriptive-analytical method that integrates doctrinal review with empirical insights, this paper analyzes the relevance and application of major sociological legal theories—such as functionalism, symbolic interactionism, Luhmann’s legal system theory, Nonet and Selznick’s responsive law, Habermas’s theory of legal legitimacy, and theories of social change and social control—in the context of medical law. The analysis demonstrates that the effectiveness of medical law depends heavily on communication, transparency, institutional culture, and the ability of legal norms to adapt to evolving social expectations and technological advancements in healthcare. The Indonesian context shows persistent challenges, including paternalistic medical culture, low legal literacy, and gaps between written norms and real clinical practice. International perspectives emphasize patient autonomy and human rights in patient care as foundational elements of modern health law. The study concludes that sociological legal theory enriches the understanding of medical law as a dynamic social system and encourages the formation of responsive, equitable, and human-centered health regulations.